2(x-4)=2x+3x

Simple and best practice solution for 2(x-4)=2x+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)=2x+3x equation:


Simplifying
2(x + -4) = 2x + 3x

Reorder the terms:
2(-4 + x) = 2x + 3x
(-4 * 2 + x * 2) = 2x + 3x
(-8 + 2x) = 2x + 3x

Combine like terms: 2x + 3x = 5x
-8 + 2x = 5x

Solving
-8 + 2x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-8 + 2x + -5x = 5x + -5x

Combine like terms: 2x + -5x = -3x
-8 + -3x = 5x + -5x

Combine like terms: 5x + -5x = 0
-8 + -3x = 0

Add '8' to each side of the equation.
-8 + 8 + -3x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = 0 + 8
-3x = 0 + 8

Combine like terms: 0 + 8 = 8
-3x = 8

Divide each side by '-3'.
x = -2.666666667

Simplifying
x = -2.666666667

See similar equations:

| 12(s+5)=7.5 | | 20x-2=36x+2 | | n^2+8n-7=0 | | 7w^2+3=-10w | | 36=16x-12x | | 4(2x)=40 | | 3x^2+x-0.5=0 | | 2(3x)=36 | | 10x+6y=16 | | -7x^2-18x+0=0 | | 2z-67=-21 | | 8-(-4)+5=12 | | 7n+3-5n=3n-6 | | V=3.14v^2h | | (25)(7)+x=175 | | -3x+6x=0 | | 0=5x^2-64x-13 | | 18+5=48 | | x-29=15 | | .5(12x-8)=9x-18 | | 5x-3-2x=2(x-4) | | 3(x+2)=5(x-1)+5 | | 0=2a^2+7a+3 | | 4(5y-3)-(8y+5)= | | 2x+5(6x-4)=44 | | 40(25+x)=1 | | 8x-14=3x-6 | | m+90=150 | | -16x^2+324=0 | | 9x+6=6x+4 | | 0=-15m^2+60 | | 8(4+x)=360 |

Equations solver categories